Memory and Aging in Context. [article]. - Hess, Thomas M.
Much research has indicated that aging is accompanied by decrements in memory peroformance across a wide variety of tasks and situations. A dominant perspective is that these ahe differences reflect normative changes in the integrity and efficiency of the information-processing system. Contextual perspectives of development, however argue for consideration of broader constellation of factors as determinants of both intraindividual variation in memory functioning. The validity of the contextual perspective in characterizing the relationshipbetween aging and memory is examined through a review of studies exploring a variety of alternative mechanisms associated with the differences in performance . It is concluded that a more multidimentional approach to the study of aging and memory is warranted.--(from the author)